The case of the Jollibee funko pop: Understanding international brand alliances and purchase motivations of limited-edition collectibles - Santos, Joseph Emil N. (Animo Repository, 2020)
Using a case-based approach, this exploratory study seeks to understand purchase and collection motivations of buyers of the Jollibee Funko Pop. It will also explore perceptions on the brand collaboration between Philippine-based Jollibee and United States-based Funko. While most studies on co-branding use simulated alliances, this study provides a real example of an international branding collaboration, thereby providing a nuanced understanding of co-branding spillover effects, and how a consumer’s willingness to identify with a brand motivates their purchase and collection decisions.